Developing Model Of Learning Reading-Literacy At Madrasah Ibtidaiyah Negeri Iii Bondowoso, East Java, Indonesia And Kebangsaan Bukit Rokan Utara School, Gemencheh, Negeri Sembilan, Malaysia For Lower Grade Students - Muhith, Abdul; Farihah, Umi; Saihan, M; A. Ghani, Muhammad Faizal (Universitas Pendidikan Indonesia, 2021)
This research is categorized as developmental research which is conducted in order to design and develop a model of learning reading-literacy for lower grade at elementary school both in Indonesia (MIN III Bondowoso, East Java) and Malaysia (Kebangsaan Bukit Rokan Utara School, Negeri Sembilan). The process of developing the model based on ADDIE development procedure. However, in this research, researchers conduct the research for two phases only which are need analysis phase and developing model phase. The data gotten from the principals, teachers at lower grade, and students at lower grade. In the need analysis process can be concluded that there are several construct must be consider in designing learning reading-literacy model. Those are 1). Learning objectives; 2). Instructional material; 3). Learning experience; 4). Learning strategy; 5). Learning literacy procedure; 6). Time allocation; 7). Monitoring; and 8). Learning resources. Those items then becoming the prior consideration in developing sub-items as part of designing learning reading-literacy model. In the designing phase, there consist of three part which are designing prototype I, prototype II, and prototype III. There were an additional items from 18 expert in prototype II toward prototype I. Those item consist of construct 1 which change from six items to 20 items; construct 2 which change from 5 items to 16 items; construct 3 which change from 3 items to 14 items; construct 4 which change from 8 items to 20 items; construct 5 which change from 2 items to 16 items; construct 6 which change from 3 items to 10 items; construct 7 which change from 1 items to 9 items; and construct 8 which change from 4 items to 9 items. While in designing prototype III, there were also several changes which change from 20 items to 19 items for construct 1; no changes for construct 2 until construct 8. There are distinction between Indonesia and Malaysia, and this is not significantly different. Those different is coming from the learning resource used in learning activities. Therefore, for this items, the developed model then divided into general resource which used same resource, Indonesian resource, and Malaysian resource (which cannot be specified).